The complete mitochondrial genome of Cenchrus fungigraminus indicates structural dynamics and sequence divergences in Poaceae family - Sheng, Wentao (Frontiers in Plant Science, 2025)
BackgroundCenchrus fungigraminus is a perennial grass species, which is used in the cultivation of edible fungi, helping to resolve land use conflicts between edible fungus cultivation and forest production. It can be also utilized for bioethanol production and fiberboard manufacturing. Currently, no report was released on the mitochondrial genome. Thus, the C. fungigraminus mitochondrial genome was assembled and annotated utilizing a combination of Illumina and PacBio sequencing data.ResultsThe assembled genome measures 404,398 bp and exhibits a linear structure. The GC content is 43. 98%, and 64 characteristic genes were identified, containing 34 protein-coding, six rRNA, 22 tRNA and two pseudo-genes, with 17 genes containing 30 introns. The mitochondrial genome codon usage displayed a significant A/T preference. A total of 235 dispersed, 93 simple sequence, and 38 tandem repeats were detected. Furthermore, 34 sequence fragments (17,634 bp) were transferred from the chloroplast to the mitochondria, accounting for 4.36% of the complete mitochondrial genome. The gene rps2 was identified as having the highest polymorphism. Additionally, these genes (ccmB, nad2, and rps7) were influenced by positive selection. Among the reported Poaceae mitochondrial genomes, the genome sizes range from 381,065 to 704,100 bp, with GC content ranging from 42.27% to 44.43%. Three genes (sdh3, rps10, and rpl6) are missing in the Poaceae mitochondrial genome, indicating significant rearrangements in the overall genome structure and low homology. It was shown that C. fungigraminus is most closely related to Saccharum officinarum within the Poaceae family by Phylogenetic analysis. The interspecific Ka/Ks comparison indicated that 28 protein-coding genes have a Ka/Ks ratio < 1.ConclusionTherefore, the mitochondrial genome data of C. fungigraminus was enriched and a theoretical basis was provided for germplasm evaluation and new variety utilization.